Potential model as a tool of understanding the recent regional structure of Hungary - Nagy Gábor (European Regional Science Association (ERSA), 2005)
The change of political and economic regime after the State Socialist period (1948-1989) and forming a neo-liberal market economy changed the spatial structure of the country very rapidly. The winner of the new era became the capital city and its' surrounding (agglomeration zone), the Budapest-Vienna axis, and the Western border region. There were some other local success stories in the countyside, but they were unable form innovative, rapidly growing zones, just became islands (cathedrals in the desert, as Castells said in 1989). This limited number of success stories formed out two basically different types of restruction and modernisation. One was connected mainly to the capital city itself, characterised by the post-industrial way of development, strenghten with the dominant role of institutions and government. The other possible path of local and/or territorial success based on re-industrialisation with close connections to FDI in electronics and automobile industries. The worldwide stagnation period in 2000-2001 weaken their position, but in paralel with the beginning of the new growing period, this areas and cities were able to fasten the development again. The service activities had no specific role in the success of the countryside, however some university-towns, R@D centres had (and have) emerging potential to form a new way of success. The used model (potential-model) has close connection to the phisical analogy, but seems a very usfull tool to see and understand the spatial form of success regions, and change of economic key-indicators. We can characterize the different type of regions (NUTS 2 level), counties (NUTS 3 level) and small-regions (NUTS 4 level) and outpoint the inner structure of their economic potential.
Keywords: 330